A Novel Method for Simultaneous Removal of NO and SO2 from Marine Exhaust Gas via In-Site Combination of Ozone Oxidation and Wet Scrubbing Absorption - Zhitao Han; Tianyu Zou; Junming Wang; Jingming Dong; Yangbo Deng; Xinxiang Pan (Journal of Marine Science and Engineering, 2020)
The stringent international regulations on marine emission abatement have exerted a huge push on the development of marine desulfurization and denitrification technologies. However, for the traditional vessels driven by large two-stroke diesel engines, simultaneous removal of NOx and SO2 is still a big challenge at present. Here, a one-stage ozone oxidation combined with in-situ wet scrubbing for simultaneous removal of NO and SO2 is proposed. A series of experiments were performed based on a bench-scale reaction system. The results showed that in-situ wet scrubbing could effectively decrease flue gas temperature, and then suppress the thermal decomposition of ozone, which was beneficial for improve oxidant utilization. Meanwhile, the in-situ combination of ozone injection and wet scrubbing was in favor of improving the selectivity oxidation of NO over SO2 by ozone, which was possibly due to the high aqueous solubility of SO2 in water. Aiming to reduce the electric power consumption by an ozone generating system, O3/NO molar ratio was kept as low as possible. A complete removal of SO2 and a high NOx removal efficiency could be achieved through the introduction of other oxidative additives in scrubbing solution. This integrated system designed for marine application was of great significance.